Yield elements of sweet corn in different population densities - Soares de Souza, Renan; Soares Vidigal Filho, Pedro; Alberto Scapim, Carlos; José Marques, Odair; Coelho Queiroz, Dyane; Shigueru Okumura, Ricardo; Vieira José, Jefferson; Verri Tavore, Rafael (Federal University of Piauí, 2013)
The objective of the present study was to evaluate the population density effect upon yieldcomponents of sweet corn during two crop years. The experimental design used was the randomizedcomplete blocks with four replications. The treatments were based on combination among sweetcorn hybrids (Tropical Plus and RB-6324) and plant populations (40,000; 55,000; 70,000; 85,000 and100,000 plants ha-1), in the factorial scheme 2 x 5, evaluated in two “Summer” crop years (2009 and2010). The characteristics evaluated were number of rows per ear, number of grains per ear row,plant prolificacy and total husked ear yield, whose average values were submitted to the jointanalysis of variance. In the year of 2009 for Tropical Plus and in the year of 2010 for RB-6324, theprolificacy decreased linearly until the maximum population of plants used, which presented valuesof 1.04 ear plant-1 and of 1.02 ear plant-1, respectively. A minimum value of prolificacy (1.08 earplant-1) was observed for RB-6324 in 2009 with 92,935 plants ha-1. In 2009, the highest yields of huskedears for Tropical Plus (8.43 t ha-1) and for RB-6324 (9.88 t ha-1) were achieved with a density of 100,000plants ha-1. On the other hand, in the second crop year, the yields increased quadratically from51,848 plants ha-1 (7.78 t ha-1), for Tropical Plus, and from 57,648 plants ha-1 (9.32 t ha-1), for RB-6324,until the maximum population of plants evaluated, whereupon presented their respective maximumvalues of 12.04 t ha-1 and 12.31 t ha-1. In general, the increase in population was unfavorable to theprolificacy of plants, but did not impair the husked ear yield, for which it was noted better answerswith a population of 100,000 plants ha-1, in both crop years and hybrids used.